REFORMULASI HUKUM PERKAWINAN ISLAM DI INDONESIA - Agus Toni (LPPM Institut Agama Islam Al-Hikmah Tuban, 2016)
As social beings, humans can not live without any legal or sebutannya- name that regulate their social life. It is inconceivable there is a communion of life that knows no sort of order-in this case-law that will govern their lives. A belief that hold true Muslims is that Islam contained in the Quran and al-Sunnah is the guidance of Allah that must guide all his life for the salvation of the human race in the world and akhira.Berbeda case with teachings never before revealed by God, the teachings of Islam are not only applicable to a particular group of people and limited to a period tertentu.Ajaran Islam since revealed to have been established as a handbook for all human groups at various places and the time until the end of masa.Hal was affirmed by Ibn Qayim in his book